The political economy of development - Meenan, James (Statistical and Social Inquiry Society of Ireland, 1958)
This Society was founded in 1847, twelve years after the British Association for the Advancement of Science had first met in Dublin. Its foundation reflected the contemporary interest in Political Economy; while its early proceedings testify to the confidence which its members felt in the science, and in themselves. Our first President was Archbishop Whately, who had been Nassau Senior's successor in the chair of Political Economy at Oxford. Addressing the Society at the end of its first session, he declared that ?next to sound religion, Political Economy is most essential to the well-being of society?.
Presidential address delivered at a Joint Meeting of the Society and Section F. of the British Association for the Advancement of Science on Friday, September 6th, 1957.
Keywords: Political economy; Economic development; Development policy; 314.15